Fermented Jelly Candy, Aspects of Lime Mixing Percentage On Its Consistency And Sensory Properties - Richardus Widodo; Wahyu Kanti Dwi Cahyanai; Anita Wulandari (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
This study aims to determine the effect of the combination of fermented noni and lime on consistency and sensory properties. The design used was a completely randomised design (CRD) with one factor, namely the ratio of fermented noni and lime, which were P1 50:50, P2 60:40, P3 70:30, P4 80:20, and P5 90:10. The study was conducted at the Integrated Agroindustry Laboratory, Faculty of Vocational Studies, Untag Surabaya. Data collection consisted of organoleptic test data from 30 panelists and analysis results, namely physical consistency analysis in the form of texture testing using a penetrometer. The analysis results indicate that the optimal formulation for fermented noni jelly candy, serving as a reference for producers to manufacture consumer-preferred fermented noni jelly candy ( ), is a 50:50 ratio of fermented noni to lime.